Prolonged impact of the COVID-19 pandemic on self-harm hospitalizations in France: A nationwide retrospective observational study. Issue 1 (13th June 2022) - Jollant, F.; Roussot, A.; Corruble, E.; Chauvet-Gelinier, J. C.; Falissard, B.; Mikaeloff, Y.; Quantin, C.
Abstract: Background: The first wave of the COVID-19 pandemic in France was associated with a reduced number of hospitalizations for self-harm, with the exception of older people. The on-going pandemic may have both sustained and delayed effects. Methods: Data were extracted from the French national hospital database (PMSI), a nationwide exhaustive database. The number of self-harm hospitalizations (ICD-10 codes X60–84) between September 1, 2020 and August 31, 2021 ( N  = 85, 679) was compared to 2019 ( N  = 88, 782) using Poisson regression models. Results: There was a decrease in the total number of self-harm hospitalizations during the studied period versus 2019 (−3.5%; Relative Risk [RR] [95% Confidence Intervals] = 0.97 [0.96–0.97]; p  < 0.0001). However, sex and age effects were identified. While adults aged 30–59-years-old showed a decrease (monthly decreases: −12.6 to −15.0%), we found an increase in adolescent girls (+27.7%, RR = 1.28 [1.25–1.31]; p  < 0.0001), notably since January 2021. Moreover, the numbers were similar to 2019 in adolescent boys, in youths aged 20–29 years, and in people aged 70 and more. Hospitalizations in intensive care units decreased (−6.7%, RR = 0.93 [0.91–0.96]; p  < 0.0001) and deaths at hospital following self-harm remained stable (+0.6%, Hazard Ratio = 0.99 [0.91–1.08], p  = 0.79). Conclusions: During this second stage, the number of self-harm hospitalizations remained at a lower level than in the prepandemic period. However, significant variations over time, age, and sex were observed. Young people (notably adolescent girls) appear to have particularly suffered from the persistence of the pandemic, while older people did not show any decrease since the beginning. Vigilance and continuing prevention are warranted.